Interfering with reconsolidation by rimonabant results in blockade of heroin-associated memory - Jiang Lin; Yilin Peng; Jinlong Zhang; Jinlong Zhang; Junzhe Cheng; Junzhe Cheng; Qianqian Chen; Binbin Wang; Yuhang Liu; Shuliang Niu; Shuliang Niu; Jie Yan (Frontiers Media S.A., 2024)
Drug-associated pathological memory remains a critical factor contributing to the persistence of substance use disorder. Pharmacological amnestic manipulation to interfere with drug memory reconsolidation has shown promise for the prevention of relapse. In a rat heroin self-administration model, we examined the impact of rimonabant, a selective cannabinoid receptor indirect agonist, on the reconsolidation process of heroin-associated memory. The study showed that immediately administering rimonabant after conditioned stimuli (CS) exposure reduced the cue- and herion + cue-induced heroin-seeking behavior. The inhibitory effects lasted for a minimum of 28 days. The effect of Rimonabant on reduced drug-seeking was not shown when treated without CS exposure or 6 hours after CS exposure. These results demonstrate a disruptive role of rimonabant on the reconsolidation of heroin-associated memory and the therapeutic potential in relapse control concerning substance use disorder.